Smart Home Automation Using Voice Recognition - Yadav, Sapna; Srivastava, Samridhi; Singhal, Megh (International Journal of Computer Sciences and Engineering, 2019)
Automation is the art that reduces human or any other entities labour its time and the cost. The sole objecting of designing this project is inventing a system for the people who are less privileged to power and use household by sitting in their chair and using their voice to improvise commands. This asset is functionally designed in a way to be helpful to them which hasn’t been profoundly implemented till date. The motivation to design this voice based home automation system especially the people suffering from disabilities like quadriplegia (who cannot move their limbs but can speak and listen) to managed household appliances to their convenience. An implementation of texting concept has also been applied for the verbally challenged. The concept of this is whenever the person needs help he/she can pronounce help and a text message would be sent to their immediate family members. This system is very useful in the case of any emergencies concerning the person.